Strategi Layanan Bimbingan Konseling Dalam Mengatasi Perilaku Bullying Peserta Didik Di Smkn 10 Luwu - Kiki Samsuddin; Taqwa; Hilal Mahmud; Tasdin Tahrim (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to reveal the strategy of guidance and counseling services in dealing with bullying behavior of students at SMKN 10 Luwu. This research aims to determine the position of the counseling guidance service and the strategies used by the counseling guidance service in overcoming the bullying behavior of students at SMKN 10 Luwu. This research is qualitative research using interview, observation and documentation study methods. The first research focus is the bullying behavior of students at SMKN 10 Luwu. Second, the counseling guidance service strategy in overcoming bullying behavior of students at SMKN 10 Luwu. Through several stages, namely; (1) Identifying internal and external factors that contribute to overcoming bullying behavior; (2) Analyze the school's position in guidance and counseling services to overcome student bullying behavior; and (3) Formulation of guidance and counseling service strategies in overcoming student bullying behavior. The results of this analysis show that the guidance and counseling service strategy in dealing with student behavior is improving communication with perpetrators and victims, providing motivation to perpetrators and victims, providing advice to perpetrators and victims, providing sanctions in the form of punishment to perpetrators